2015
DOI: 10.1021/acscatal.5b00057
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Fischer–Tropsch Synthesis: Chemical Nature of the Oxide Support as a Performance Descriptor

Abstract: The effect of the chemical nature of the oxide support on the performance of cobalt Fischer–Tropsch catalysts is investigated. A series of supports is synthesized via monolayer coverage of porous γ-Al2O3 with various oxides representative of a wide range of Lewis acid–base character, as quantified by UV–vis spectroscopy coupled to alizarin adsorption. Incorporation of cobalt (20 wt %) results in model catalysts with identical porosities and similar Co particle sizes (>10 nm), allowing the study of support effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 67 publications
5
86
0
Order By: Relevance
“…They reported that zeolite catalysts which owned higher quantity of the acidic centers with medium strength showed also higher isomerization activity in Fischer-Tropsch synthesis. Prieto et al [31] claimed that the overall reaction rate of the F-T synthesis carried out on cobalt catalysts reaches a maximum for oxide supports characterized by an intermediate acid-base character. Such activity behaviour authors related with the nature of the support.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that zeolite catalysts which owned higher quantity of the acidic centers with medium strength showed also higher isomerization activity in Fischer-Tropsch synthesis. Prieto et al [31] claimed that the overall reaction rate of the F-T synthesis carried out on cobalt catalysts reaches a maximum for oxide supports characterized by an intermediate acid-base character. Such activity behaviour authors related with the nature of the support.…”
Section: Resultsmentioning
confidence: 99%
“…Prieto et al reported that the methane selectivity is at a maximum as a function of the acid–basic character of the support, and that a highly basic dopant such as SmO x can suppress methane formation. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Contrariwise, the CoZrAl ME catalyst, which presented a homogeneous distribution, showed a lower activity than the CoAl catalyst. Unfortunately, these results cannot be explained by differences in support acidity, factor that is believed to play a crucial role in the FTS activity [46,47]. According to Johnson and Bell [33], promotion with Zr originates from sites with enhanced activity at the Co-ZrO 2 interface.…”
Section: Activity and Stability Of The Catalystsmentioning
confidence: 99%
“…Prieto et al [46] found that the TOF and the selectivity to long chain hydrocarbons increases with increasing acidity of the oxide support. However, excessive acidity leads to a partial coverage of the cobalt particles by partially reduced oxide support species.…”
Section: Physicochemical Properties Of the Supportsmentioning
confidence: 99%
See 1 more Smart Citation